SEA SURFACE SALINITY AND PRECIPITATION PATTERNS AS INDICATORS OF CLIMATE CHANGE-INDUCED HEALTH RISKS IN INDONESIAN COASTAL VILLAGES: A DATA ENVELOPMENT ANALYSIS APPROACH - Wati, Dyah Retno (Jurnal Manajemen Kesehatan Indonesia, 2024)
Coastal communities in Indonesia face interconnected challenges from climate change and public health vulnerabilities, yet the relationships between these factors remain poorly understood. We investigated these connections across eight Indonesian provinces by analyzing marine dependency, disease susceptibility, and flood risk projections using Data Envelopment Analysis (DEA) and multiple datasets. Our analysis revealed that South Kalimantan's coastal communities are particularly vulnerable, demonstrating the highest dependency on marine resources while simultaneously facing significant health and environmental challenges. This heightened vulnerability is evidenced by elevated Marine Capture Fisheries Households (RTPT) scores and fish capture data, indicating substantial economic reliance on marine resources. The challenges are further intensified by projected flood risks expected to impact these areas within six years, alongside varying health vulnerabilities including tuberculosis, HIV, dengue fever, and COVID-19 cases. Through our DEA estimation, which incorporated six output and four input variables along with demographic information, we found that South Kalimantan's marine resource dependency significantly exceeds that of other provinces. These findings provide crucial insights for policymakers and health administrators, establishing a data-driven foundation for developing targeted interventions and resource allocation strategies. Our study underscores the necessity of implementing integrated approaches that simultaneously address environmental and public health concerns in coastal communities.